COMMUNICATION AND FAMILY INTEGRATION - Barberán, María Fernanda Zambrano (International Journal of Psychosocial Rehabilitation, 2020)
This paper refers to some aspects related to poor family communication between parents and children because it is an issue that has always aroused interest in researchers and teachers. The objective was to analyze the incidence of communication in family interaction in the Educational Unit “San Cayetano de Chone” and look for communication strategies that help them build a good basis for their emotional relationships with their children. The methodology was descriptive with a qualitative and quantitative approach; The bibliographic method was used for the theoretical support of the research variables at local, national and international levels. The technique applied was the survey of 3rdgrade students. of Baccalaureate, and an interview with the psychologist of the Educational Unit "San Cayetano de Chone". The population that was selected was 206 students with a sample of 150 people involved in this research, for a significance level of 0.05. The results obtained allowed us to show that there are differences in communication for family interaction between parents and children, which significantly influences the socio-educational development and psychosocial adjustment of the student’s object of this study.